An introduction to community development (Routledge, 2015)
"Beginning with the foundations of community development, An Introduction to Community Development offers a comprehensive and practical approach to planning for communities. Road-tested in the authors' own teaching, and through the training they provide for practicing planners, it enables students to begin making connections between academic study and practical know-how from both private and public sector contexts. An Introduction to Community Development shows how planners can utilize local economic interests and integrate finance and marketing considerations into their strategy. Most importantly, the book is strongly focused on outcomes, encouraging students to ask: what is best practice when it comes to planning for communities, and how do we accurately measure the results of planning practice? This newly revised and updated edition includes: - increased coverage of sustainability issues, - discussion of localism and its relation to community development, - quality of life, community well-being and public health considerations, - and content on local food systems. Each chapter provides a range of reading materials for the student, supplemented with text boxes, a chapter outline, keywords, and reference lists, and new skills based exercises at the end of each chapter to help students turn their learning into action, making this the most user-friendly text for community development now available"--Provided by publisher.